Effects of characteristics of douchi during rapid fermentation and antioxidant activity using different starter cultures. (26th January 2023) - Hou, Hongwei; Zhou, Wanting; Guo, Lidan; Jia, Shuang; Zhang, Xiaoyan; Wang, Liping
Abstract: BACKGROUND: As a traditional Chinese condiment, douchi has attracted attention in Asian and European countries because of its high nutrient content and unique flavors. Douchi is currently produced mostly by natural fermentation. The quality of douchi produced in this way is affected by microbial species, temperature, humidity, and season, so the physical and chemical properties of the product, the content of flavor substances, and its safety vary. In this study, four safe strains with high protease activity, screened previously, namely Bacillus velezensis, Bacillus amyloliquefaciens, Lichtheimia ramosa, and Lichtheimia corymbifera, were used as starter cultures for douchi fermentation. RESULTS: After 35 days, the results showed that the pH, titratable acids, free amino‐type nitrogen, amino acids, the total number of colonies, and neutral protease activity of all samples had reached an average level. Through gas chromatography–mass spectrometry (GC–MS), the content of key aroma substances aldehydes and esters was higher than in commercial douchi and the free amino acid content of douchi fermented by the four strains was three to five times that of commercial douchi. Douchi fermented by Bacillus amyloliquefaciens had more flavor substances and the highest 2, 2‐diphenyl‐1‐(2, 4, 6‐trinitrophenyl) hydrazyl (DPPH) free radical scavenging rates of 92.4%. Four samples yielded total phenolic content and soy isoflavones in the range of 0.98–1.93 g kg −1 and 0.58–0.89 g kg −1, respectively. CONCLUSION: These findings indicate that the use of a high‐protease activity starter to produce douchi can improve the quality of douchi to a certain extent. The douchi obtained using Bacillus amyloliquefaciens not only has a good flavor but also has a high level of antioxidant activity. © 2023 Society of Chemical Industry.